Lack of hidden complement fixing IgM rheumatoid factor in adult seronegative rheumatoid arthritis. Issue 1 (February 1980) - Robbins, D L; Moore, T L
Abstract : IgM rheumatoid factors capable of complement fixation and activation are commonly present in the sera of adults with rheumatoid arthritis. Hidden complement fixing IgM rheumatoid factor has been demonstrated in the majority of patients with juvenile RA and hidden agglutinating IgM rheumatoid factors have been demonstrated in the serum of adults with seronegative rheumatoid arthritis. We studied 27 adults with seronegative rheumatoid arthritis and were unable to demonstrate hidden complement fixing IgM rheumatoid factor in their sera.